2019
DOI: 10.1002/pds.4735
|View full text |Cite
|
Sign up to set email alerts
|

Use and safety of disease‐modifying therapy in pregnant women with multiple sclerosis

Abstract: Purpose The purpose of this study is to describe dispensing patterns and comparative safety of disease‐modifying therapies (DMTs) during pregnancy in women with multiple sclerosis (MS). Methods We identified pregnancies from the Truven Health Marketscan® Commercial Claims and Encounters Database (2011‐2015) and ascertained MS before delivery from inpatient and outpatient claims. We computed the proportion of women with DMT dispensing claims around pregnancy and estimated risk ratios of spontaneous abortion, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The drugs that were studied the most were interferon, glatiramer acetate, natalizumab. There were very few patients included that were treated with fingolimod, azathioprine or rituximab, MacDonald et al [ 12 ] did not stratify their analyses by type of drug and only conducted their analyses as overall. Therefore, it was not possible to include their data in the drug-specific analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs that were studied the most were interferon, glatiramer acetate, natalizumab. There were very few patients included that were treated with fingolimod, azathioprine or rituximab, MacDonald et al [ 12 ] did not stratify their analyses by type of drug and only conducted their analyses as overall. Therefore, it was not possible to include their data in the drug-specific analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The cases of polydactyly were present in β-interferon and natalizumab patients and the club foot in patients exposed to GA and natalizumab. The biggest study did not list the major malformations [ 12 ]. We contacted the authors and they stated that given that the study was performed in claims database it was not permitted to publish non-aggregated data.…”
Section: Discussionmentioning
confidence: 99%
“…54 Conversely, women with MS may have an increased risk of infection during pregnancy, particularly genitourinary and upper respiratory infections. 53,58 The Impact of Pregnancy on MS Course The Impact of Pregnancy on the Short-Term Course of MS Most of the current knowledge about the evolution of MS during pregnancy and after delivery has been obtained from the multicenter Pregnancy in Multiple Sclerosis Study, [59][60][61] which was the first prospective study to explore the relationship between pregnancy and MS. This study included untreated women with MS, most of whom were in their first pregnancy.…”
Section: Effects Of Ms On Fertility Pregnancy and Childbirthmentioning
confidence: 99%
“…33 A study of pregnant women with and without MS showed a higher incidence of lower respiratory tract infection (5.2% vs. 3.9%, respectively), but this difference did not reach statistical significance. 34 Houtchens et al, 32 using an administrative claims database, reported that women with MS had a higher risk of infection complicating pregnancy than women without MS. Using other databases, MacDonald et al 34 also found a higher risk of infection among women with MS, including a higher risk of genitourinary infections (aRR = 1.26 [1.17-1.36]) and upper respiratory tract infections (aRR = 1.33 [1.20-1.45]).…”
Section: Infectionmentioning
confidence: 99%
“…Studies of pregnant women with MS, however, showed no increased risk for hemorrhagical complications. 28,32,34…”
Section: Hemorrhagementioning
confidence: 99%